ENT 530 Social Media Portfolio / Muhammad Amir Syahmi Mohd Azhari - Mohd Azhari, Muhammad Amir Syahmi (2019)
This business started on 15 October 2019, a few day after we got our certificate from Suruhanjaya Syarikat Malaysia (SSM). I have registered this business under SSM using the name of Dot 2 Loot Market. This business was inspired by the online gaming community in Face book.